Overcoming self-confidence of Islamic religious education students: The influence of personal learning model - Hamzah Hamzah; Desi Sukenti; Syahraini Tambak; Wisudatul Ummi Tanjung (Intelektual Pustaka Media Utama, 2020)
Research on student confidence has been done a lot, but the focus in the field of personal learning models has not been found. This study aimed to determine the strengthening of personal learning models in developing student self-confidence. A total of 688 students were recruited as research samples using questionnaires as data collection techniques, and analyzed using simple linear regression. This research found that personal learning models can significantly develop students' self-confidence in Islamic Religious Education subjects. The personal learning model used by the teacher is quite strong in overcoming students' self-confidence in learning Islamic religious education. Predictable, if the personal learning model is maximally applied by Islamic religious education teachers in learning, to be